解方程组:(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9
来源:学生作业帮助网 编辑:六六作业网 时间:2024/11/17 13:22:28
解方程组:(x+2y)÷3=(2y-3z)÷6=(x-3z)÷91/2x+y-3/2z=9(x+2y)÷3=(2y-3z)÷6=(x-3z)÷91/2x+y-3/2z=9解方程组:(x+2y)÷3=(
解方程组:(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9
解方程组:(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9
(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9
解方程组:(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 1/2 x+y-3/2 z=9
(x+2y)÷3=(2y-3z)÷6=(x-3z)÷9 ,
变为2(x+2y)=2y-3z,3(x+2y)=x-3z,
又变为2x+2y=-3z=2x+6y,
∴y=0,x=-3z/2,①
1/2 x+y-3/2 z=9,②
把①代入②,-9z/4=9,z=-4,
代入①,x=6,
∴{x=6,
{y=0,
{z=-4.
解方程组 z=x+y 2x-3y+2z=5 x+2y-z=3
解方程组{z=x+y 3x-2y-2z=-5 2x+y-z=3
解方程组 :X+Y-3Z=1 Y+Z-3X=2 Z+X-3Y=3
解方程组:2x+y+z=-4 x+2y+z=-2 x+y+2z=3
3x-y+z=3,2x+3y-z=12,x+y+z=6解方程组
解方程组 x+y+z=2 x-2y+z=-1 x+2y+3z=-1
解方程组:x-2y+z=-1,x+y+z=2,x+2y+3z=-1
解方程组{3x+y-z=4,2x-y+3z=12,x+y+z=6}
解方程组{2x+3y+z=11,x+y+z=0,3x-y+z=-2.
解方程组2x+3y-z=12,3x-y+z=4,x+y+z=6
解方程组 x+y+z=5 2x-y-z=4 3x-2y-z=9
解方程组x+y+z=6 x+2y-3z=4 2x-y+z=5
x+y+z+2,4x+2y+z+2,9x+3y+z=6解方程组
解方程组x+y/2=z+x/3=y+z/4①x+y+z=27②
解方程组x-4y+z=-3,2x+y-z=18,x-y-z=7.
解方程组x+y-z=0,2x+y+z=7,x-3y+z=8
解方程组:x+y+z=4,x+y+2z=5,3x+y-z=6
解方程组:x:y:z=1:2:3;x+y+z=12,求,x,y,z的值